Retropharyngeal Calcific Tendonitis Mimics a Retropharyngeal Abscess - Natasha Pollak; Sonya Wexler (Case Reports in Otolaryngology)
Retropharyngeal calcific tendonitis (RCT) is an uncommon, self-limiting condition that is often omitted in the differential diagnosis of a retropharyngeal fluid collection. This condition mimics a retropharyngeal abscess and should be considered when evaluating a fluid collection in the retropharyngeal space. Although calcific tendonitis at other sites has been well described in the medical literature, it appears that this entity has been underreported in the otolaryngology literature where only a few case reports have been identified. Presumably, the actual incidence is higher than the reported incidence, due to lack of familiarity with this disorder. As an otolaryngologist’s scope of practice includes the managements of retropharyngeal lesions, it is important for the otolaryngologist to recognize the presentation of acute RCT and be familiar with appropriate treatment strategies. Retropharyngeal calcific tendonitis presents with neck pain, limitation of neck range of motion and includes inflammation, calcifications, and a sterile effusion within the longus colli muscle. Treatment is medical with nonsteroidal anti-inflammatory medications. RCT does not require surgical treatment, and an accurate diagnosis can prevent unnecessary attempts at operative drainage. In this study, we discuss two cases of RCT, summarize the salient features in diagnosis, including key radiologic features, discuss treatment options, and review the literature.